Tendencies of coal industry development in Ukraine - Snihur, V.; Malashkevych, D.; Vvedenska, T. (Розробка родовищ, 2016)
Purpose. Analysis of the current state and prospects of Ukraine coal industry development until 2020. Methods. Complex analysis of data regarding mine productivity, coal reserves, mine funds as well as coal consump-tion and electricity generation has been presented in the paper. The studies of statistics related to geological and extraction thickness in longwall faces are discussed. Findings. The current state of Ukraine coal mining industry and prospects of its development for the period until 2020 are considered. The analysis of Ukraine mine fund conditions is carried out. Statistical data of gross coal pro-duction at state-maintained and private mines are given. The reasons for low profitability and coal production decline in the country are considered. Results of the research into ash content of extracted coal, formation and accumulation of mine waste are interpreted. The main promising trends of efficient energy resources use and reduction of environ-mental impact on coal-mining regions are emphasized.